Akses Masyarakat Adat Terhadap Tanah Ulayat: Studi Kasus pada Masyarakat Adat Minangkabau - Al Hafidh; Krisdyatmiko Krisdyatmiko (Department of Social Development and Welfare, Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2020)
This article explores how the Bawan Nagari community access their customary land after the Indonesian political reform in 1998, leading to grant social rights' all citizens. To gain further understanding of this topic, the case study method is employed to grasp further complex and detailed issues comprehensively. This study found that community access to customary land faces several challenges stemming from internal and external factors. Internal factors stem from the indegenious tradition system adopted at Nagari Bawan, where the greater dominance to customary leaders in decision making has led to abuse of power. While external factors concerning the formal regulatory framework is suffering from in-contextualized with the current conditions and has not able in accommodating the implementation of customary law that relevant to the current situation; especially the establishment of legal instrument that closely related to the legal protection of customary rights holders.